Investigation of electron transfer between single plasmon and graphene by dark field spectroscopy. (2nd December 2020) - Du, Qian; Dou, Zheng; Zhang, Wenjia; Krüger, Katja; Zhao, Shuang; Yue, Zhao; Liu, Guohua
Abstract: We investigated the electron transfer time between single plasmonic gold nanoparticles and graphene with our home-build spectral imaging dark-field microscope. The process of electron transfer is supposed to be shuttling of hot electrons on the nanoparticle-graphene interface, resulting in a slight broadening of the scattering spectrum. For detecting the minor spectrum broadening, we firstly characterized our setup systematically and then calibrated its intrinsic error. We found the mechanism of a common but normally neglected setup error, scattering spectrum broadening, which is caused by the bandwidth of the incident light and could exist in most fast dark-field microscopy setups. We corrected the linewidth of plasmon scattering spectra theoretically by both numerical and analytical solution, and then realized it experimentally by tuning the bandwidth of the incident light. After calibration, we revisited scattering spectra of 700 small aspect ratio nanorods on glass and monolayer graphene revealing a typical 14.3 meV linewidth broadening. Furthermore, we measured four other kinds of gold nanoparticles on glass, mono- and bilayer graphene for deeper understanding of the electron transfer. A common linewidth broadening is found for each kind of particle agreeing well with previous theory. However, an unconventional linewidth narrowing is also discovered for big particles whose resonance wavelength is close to the near infrared region. It implies a competitive mechanism in the electron transfer process which could not only increase the damping of small particles, causing a linewidth broadening, but also simplify the electric field pattern for big particles, leading to a linewidth narrowing, according to our Mie theory simulation.